Effects of high-sensitivity C-reactive protein and left ventricular hypertrophy on cognitive function in hemodialysis patients - Yu Zhang; Yu-lu Gu; Wan-fen Zhang; Xiao-ping Li; Lin-fang Xu; Tong-qiang Liu (Renal Failure)
Objectives To examine the effects of high-sensitivity C-reactive protein (hs-CRP) and left ventricular hypertrophy (LVH) on the cognitive function of hemodialysis (HD) patients, and to explore the relationship between hs-CRP, LVH, and cognitive impairment (CI).Methods A cross-sectional study was conducted on 232 HD patients. Besides, general clinical data were gathered, and patients’ cognitive functions were assessed using the Beijing version of the Montreal Cognitive Assessment (MoCA-BJ). CI risk factors were screened using logistic regression modeling based on hs-CRP values (low risk <1 mg/L, intermediate risk 1–3 mg/L, and high risk >3 mg/L) and LVH status (normal and hypertrophic) groupings. The synergistic effect of hs-CRP and LVH on CI was also analyzed using the EpiR package.Results Among HD patients, 122 (52.59%) patients had CI. Multifactorial logistic regression analysis showed that the following factors were associated with an increased risk of CI in HD patients: age (OR = 1.048; 95% CI 1.014–1.083; p = 0.005), LVH (OR = 3.741; 95% CI 1.828–7.657; p < 0.001), and high-risk hs-CRP levels (>3 mg/L; OR = 3.238; 95% CI 1.349–7.768; p = 0.009). In addition, there was a significant synergy between hs-CRP high risk (>3 mg/L) and LVH.Conclusion Age, LVH, and high risk of hs-CRP (>3 mg/L) were independent risk factors for CI in HD patients. Moreover, HD patients with both hs-CRP high risk (>3.0 mg/L) and LVH were at higher risk of developing CI, and lowering hs-CRP levels and preventing LVH may prevent CI.